Combined Use of eDNA Metabarcoding and Bottom Trawling for the Assessment of Fish Biodiversity in the Zhoushan Sea - Zhou, Shan; Fan, Chenrong; Xia, Haoming; Zhang, Jian; Yang, Wei; Ji, Dengjie; Wang, Lei; Chen, Li; Liu, Nannan (Frontiers in Marine Science, 2022)
With the increase in fishing intensity and the intensification of marine pollution, the fishery resources in the Zhoushan Sea are seriously degraded, and the difficulty of censusing fish diversity hampers effective management in marine fishes. eDNA metabarcoding and bottom trawl methods were used to determine the ability of the methods to distinguish fish assemblages in the Zhoushan Sea. The species composition and diversity of the Zhoushan Sea were assessed via high-throughput sequencing analysis of environmental DNA coupled with bottom trawl fishery survey data, after which the two methods were compared. Environmental DNA screening identified 38.2% more fish species than bottom trawls. Combining these two methods, 33 orders, 65 families, and 130 species of fish were identified. Perciformes and Clupeiformes, the most abundant species in the catch, represented 31.5% and 10.0% of the total fish abundance, respectively. The results of ANOSIM and redundancy analyses indicated that the fish community structure varied significantly between summer and winter, with depth and temperature being the main environmental factors influencing fish distribution. The biodiversity index was higher in summer than in winter. Thus, our work provides more detailed seasonal data on biodiversity in the Zhoushan Sea, which is essential for the long-term management and conservation of coastal biodiversity. Compared with traditional survey methods, eDNA determination is highly sensitive, accurate, and cost-efficient, and is therefore suitable for fish diversity studies in relevant sea areas. Although this approach cannot completely replace traditional methods, our findings demonstrate that it provides a reliable complementary method for assessing fish diversity in marine ecosystems.